IMPROVEMENT AND SYSTEMATIZATION IN BUILDING MAINTENANCE MANAGEMENT MALAYSIA LIQUEFIED NATURAL GAS SDN BHD - Kamarudin, Mohd Afidz Ainul (Universiti Teknologi PETRONAS, 2017)
People invest a lot in maintaining a building. Obtaining maximum benefit in maintaining a building is what Maintenance Management is. In Malaysia, Building maintenance is improving regardless of size, location, type and ownership. The current management in Malaysia are more to reactive based and the condition of the building itself. If there are flaws in that building, then people will react. If not, most of the Building Maintenance work are not been done. The delicateness in the procedure are the top problem because it is not tally with the needs of the building users. Hence in this research, we need to identify the relationship between individual and company working structure that might effect to the poor building maintenance management. Not only that, we also need to identify the common technical problem that always occur on a building based on engineering fault and what are the ways to overcome the problems. Maintenance management must be done with the needs of the building users in order to provide them the best facilities and safe workplace. It will take consideration of both objective ad subjective needs of building users. Building maintenance is also done to ensure the building is fit and meets all the statutory requirements.